The Availability of E-Modules As a Learning Media In Problem Based Learning At SMA N 11 Pekanbaru - Siti Risna Wati; Sepita Ferazona; Suryanti Suryanti; Ibnu Hajar; Fitriyeni Fitriyeni (Universitas Lampung, 2023)
This research is a preliminary study that aims to determine the availability and feasibility of the E-Module, as well as the views of students and teachers on teaching materials that have been used so far in SMA Negeri 11 Pekanbaru. This study uses a survey method. In the research instrument used is a questionnaire. The research sample was 50 high school students and 1 Biology teacher. The results showed that from the student's perspective on the Development of Biology E-Module Teaching Materials as a whole, it has an average percentage of 78.7% in the Good category. The highest student response was the question whether you were enthusiastic about participating in the biology learning process in class? With a percentage of 100% in the Very Good category, and the lowest student response is the question Have you used textbooks or other handbooks for biology learning? With a percentage of 49.1% in the Enough category. Meanwhile, from the perspective of the teacher as a whole, it has an average percentage of 70.66% in the Good category. The teacher's response was highest in the question Did your biology learning process make students more enthusiastic about participating in learning? With a percentage of 100% in the Very Good category, and the lowest teacher response is the question Have you ever used E-modules for the learning process? With a percentage of 25% in the Less category. Based on the results of this study it can be concluded that from the perspective of students and teachers it is necessary to develop E-Modules based on Problem Based Learning (PBL), as teaching materials for class XI in SMA/MA to increase students' knowledge of Biology subject matter.Â DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27247